Issues and solutions on Inventive Problems-Solving Skills (IPSS) in invention course - Tee, Tze Kiong; Abd Nasir, Nuraliah; Azid, Nurulwahida; Mohamad, Mimi Mohaffyza; Wu, Ming Chang; Swaran Singh4, Charanjit Kaur (2022)
Inventive Problem-Solving Skills (IPSS) is the ability to solve difficulties efficiently and without hindrance. The aim of this study is to identify issues, importance, and solutions in identifying the causes of inventive design problems among students and teachers of Invention. In addition, there are two objectives of the study (1) to identify the differences in the importance and issues of IPSS among students and teachers of Invention, and (2) to identify the importance, issues and proposed solutions of IPSS by Invention’s teachers. This study has a used mixed-method an approach that includes quantitative and qualitative methods. For the first objective quantitative will be used by making a questionnaire while for the second objective, the mixed method was used by using questionnaires and semi-structured interviews. The survey covered a total of 133 students and 30 Invention teachers from a secondary school in Johor. In this study, SPSS software was used to obtain the data. As a result, there was no significant difference in significance [t (133) = 2.915; p = .194, (p > .05)] or problem [t (133) = .142; p = .09, (p > .05)] for gender, according to t-test findings. The level of significance was then determined using a two-way ANOVA test. Subsequently, two-way ANOVA tests revealed that importance (F (30) = 2.874, p = .061) and problem (F (30) = 6.846, p = .112) abilities were not influenced by teacher gender or teaching experience. To identify the root cause of inventive problems, the majority of teachers prefer to use Functional Analysis to apply the Theory of Inventive Problem-Solving Skills (TRIZ). As a result, the creation of self-learning modules is offered as a teaching resource to help students use their abilities in the Invention course. Thus, the objective has been well achieved to (1) identify the differences in importance and issues of IPSS among students and teachers of Invention, and (2) identify the importance, issues and proposed solutions of IPSS by Invention’s teachers. Among the challenges faced in this study was that communication between students and teachers was done virtually on deck due to the Covid-19 issue that struck.